2007
DOI: 10.1080/14767050701483389
|View full text |Cite
|
Sign up to set email alerts
|

ADAM12 as a marker of trisomy 18 in the first and second trimester of pregnancy

Abstract: ADAM12 may be a useful addition to early screening for trisomy 18 alongside other chromosomal anomalies, particularly if biochemical screening can occur before 10 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 39 publications
(61 reference statements)
2
19
0
Order By: Relevance
“…Following correction for gestational age and maternal factors, the current study was unable to support this. Our data support findings from previous studies where ADAM-12 levels have been shown to be positively correlated with PAPP-A [19, 32,40] . In addition, we have also shown ADAM-12 and PP13 levels to correlate.…”
Section: Discussionsupporting
confidence: 83%
“…Following correction for gestational age and maternal factors, the current study was unable to support this. Our data support findings from previous studies where ADAM-12 levels have been shown to be positively correlated with PAPP-A [19, 32,40] . In addition, we have also shown ADAM-12 and PP13 levels to correlate.…”
Section: Discussionsupporting
confidence: 83%
“…For example, ADAM12 (a disintegrin and metalloprotease 12) shows evidence of positive selection on the primate stem lineage ( ω =8.155, p=0.00691, PSS%=0.83%). ADAM12 mediates syncytiotrophoblastic shedding of oxytocinase [49] and its reduced maternal serum concentrations were reported in early pregnancies that are complicated with fetal trisomies 18 and 21 [50], and in pregnant women who subsequently developed preeclampsia [51]. FN1 (fibroncetin 1) shows evidence for positive selection on the Euarchontoglires stem lineage ( ω =170.096, p=0.0225, PSS%=0.06%).…”
Section: Discussionmentioning
confidence: 99%
“…ADAM12 has been studied as a first trimester marker for predicting pre-eclampsia [8][10], aneuploidy [8], [10][15] and small-for-gestational age fetuses [16], [17]. A clear biological explanation for the decreased level of ADAM12 in EPs does not exist; however, the predominant theory involving impaired placentation could account for ADAM12 playing an important role in the growth and function of the placenta [8].…”
Section: Discussionmentioning
confidence: 99%